The Implication of Mastectomy Flap Fixation in Decreasing the Incidence of Seroma on Breast Cancer Patient - Kustono, Patric Christ Ardhika; Purwanto, Heru (Folia Medica Indonesiana, 2021)
Highlight: • Modification of radical mastectomy with flap fixation treatment in seroma production in breast cancer patients was analyzed. • The number of seromas from the drain removal time in patients undergoing modified radical mastectomy with flap fixation was reduced. Abstract: Seroma is the most common complication after mastectomy procedure. This study was conducted to analyse the treatment of flap fixation in seroma production after modified radical mastectomy in breast cancer patients. An interventional prospective clinical study in 35 female patients with breast cancer who underwent modified radical mastectomy with flap fixation in the period August-December 2018 and 35 patients without flap fixation through historical data of patient who underwent modified radical mastectomy in the period 2016-2017 at RSUD Dr. Soetomo Surabaya. Data of characteristic patients will be presented descriptively and analyzed statistically using the appropriate test. The result of the statistical test using Chi Square with a 95% significance level obtained a value of p = 0.000 (p <0.05), it was said statistically that there was a significant relationship between the treatment of flap fixation and the time of releasing drain in this study. The treatment of flap fixation will reduce drainage time by <10 days. The results of the odds ratio (OR) obtained OR = 16 and CI: 95% (4.094 – 62.528) which means that the treatment of flap fixation will reduce the releasing time of the drain 16 times more effectively than not performing flap fixation. Correlation between the treatment of flap fixation and the time of releasing drain was considered to be moderately positive (Contingency Coefficient Chi Square = 0.476). There was a significant reduction in the number of seroma assessed from the time of releasing drain faster in patients who underwent modified radical mastectomy with flap fixation.